2019
DOI: 10.17532/jhsci.2019.795
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of orofacial trauma in soccer players of a Brazilian club

Abstract: Introduction: The objectives of the study were to evaluate the prevalence of orofacial injuries in soccer players of a Brazilian club, considering the category, the position in the field, and the most affected anatomic site, through medical records. Methods: A total of 126 charts of players from the base categories (sub-15, sub-17, and sub-20) and male and female professional categories from 2016 to 2018 were evaluated. It was considered inclusion criteria to be a soccer player hired by a club in the ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The most frequent orofacial injuries were sustained by goalkeepers, who at the same time most frequently used mouthguards. To date, no similar study has been conducted in Croatia, while there are few studies worldwide 2,27 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most frequent orofacial injuries were sustained by goalkeepers, who at the same time most frequently used mouthguards. To date, no similar study has been conducted in Croatia, while there are few studies worldwide 2,27 …”
Section: Discussionmentioning
confidence: 99%
“…However, a similar study conducted in Brazil found the opposite. Their study found that respondents in the professional football category had a greater awareness of dental trauma prevention than amateur football players, which is probably an indicator of the technical capabilities of professional football clubs, which have a more comprehensive range of insurance policies to prevent injuries and trauma 27 . The listed data are consistent with the study of the incidence of dental trauma in Izmir, where it was found that amateur football players suffer injuries and trauma more frequently than professional football players, which can be attributed to a lower level of development of developed skills and possibilities in the game 24 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation